Mikroprosesor Intel 8086/8088, 80186/80188, 80286, 80386, 80486, Pentium, Posesor Pentium Pro, Pentium II, Pentium III, dan Pentium 4 : Arsitektur, pemrograman, dan antarmuka - Brey, Barry B. (Andi, 2005)
x, 685-1018 p. : il.; 29 cm.